MEMBANGUN RULE DENGAN ALGORITMA ITERATIVE DICHOTOMISER 3 (ID3) UNTUK PENJURUSAN SISWA SMA - Didik Kurniawan; Anie Rose Irawati; Hilman Hudaya (Jurnal Komputasi, 2014)
Indonesian Senior High School has a policy to decide the majors for the student that match their interests, talents and abilities. By developing an auto learning decision support system with iterative dichotomiser 3 (ID3) algorithms help the teachers to make decision for student majoring. ID3 algorithms is a part of learning techniques of artificial intelligence. By using data sample from the past as training data, the system then will be able to give a decision support that can be used as a reference for teachers to majoring students. To get a good decision accuracy required training data with wide variation. The result showed the more vary of training data the higher accuracy of the decision result.